2022
DOI: 10.1097/iae.0000000000003505
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Membrane Graft for the Treatment of Large Refractory Macular Hole

Abstract: This study was conducted to demonstrate refractory macular hole closure with human amniotic membrane graft and to evaluate type of closure Type I versus Type II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…PVR and retinal redetachment are common sequalae of intraocular bodies, especially in younger patients. 1 While it is possible that the introduction of the 3-layer plug in our case promoted PVR formation, human amniotic membrane has been used intraocularly in other instances, such as for macular hole repair, 10 retinal detachment, 11 optic disc pit maculopathy (ODPM), 12 and a choroidal patch. 13 Fibrin glue 14 and scleral patch graft 15,16 have also been used in ODPM.…”
Section: Discussionmentioning
confidence: 93%
“…PVR and retinal redetachment are common sequalae of intraocular bodies, especially in younger patients. 1 While it is possible that the introduction of the 3-layer plug in our case promoted PVR formation, human amniotic membrane has been used intraocularly in other instances, such as for macular hole repair, 10 retinal detachment, 11 optic disc pit maculopathy (ODPM), 12 and a choroidal patch. 13 Fibrin glue 14 and scleral patch graft 15,16 have also been used in ODPM.…”
Section: Discussionmentioning
confidence: 93%
“…The human amniotic membrane plug was first used to promote the closure of recurrent MH 17,22 and was later used for treating myopic MHs with RD. 14,15 It was also used for repairing RD with PRBs located above PCRA in PM.…”
Section: Discussionmentioning
confidence: 99%
“…23 We also found that the LhAM plug might hinder the repair of the outer structure of the retina because it might stay between the retina and the retinal pigment epithelium for a long time. 17 In our previous study, we used autologous bloodassisted LhAM graft covering to treat eyes with MH in high myopia and showed that the MH closure rate was 83.3% postoperatively, and the surgical trauma was minimal. This was because the LhAM graft was placed right on the surface of the retina.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations